(3GdChQGb GdJLGQjI hGdYedjGJ GdeUQajI (B/s - (3jGedcj, CcQes ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3ejRI gPG GdcJGH Cfg dG jbJUQ Ydi HSW CMcGe GdbGfhf GdCQOfj hMOgG hEfeG dYbOg debGQfI HjfgG hHjf eG jge GdbGQF GdEWdGY Ydjg ef CMcGe aj GdbhGfjf GdCNQi, dPG YQa GdcJGH HOGjI HGdChQGb GdJLGQjI, Ke LGA Ydi PcQ SfO GdSMH hJOGhdg, hbHhdg, hVeGfGJg hCNjQG JbGOe GdOYGhj GdfGTFI ef SfO GdSMH Ke Cced GdehVhY HPcQ GdTjc, aYQa Hg, hHNUGFUg hVeGfGJg Ke fGbT GdYedjGJ GdeUQajI hGdMSGH GdLGQj GdeUQaj hhOjYI GdfbhO hELGQI GdUfGOjb GdMOjOjI haJM GdGYJeGO GdeGdj hGdGYJeGO GdeSJfOj hNWGH GdVeGf(B.s
(3HHdjhLQGajI (B: (3UaMI (B349-351.s
Keywords: (3GdChQGb GdJLGQjIs -- (3bhGfjf hJTQjYGJs; (3GdHfhcs -- (3bhGfjf hJTQjYGJs